STRENGTHENING THE WAQF PRODUCTIVE-BASED ECONOMY IN TAKMIRS AND CONGREGATION OF MASJID AL HIDAYAH WONOGIRI WITH THE “ABCD” APPROACH - Fuad Hasyim; Ahmad Indarta; Agus Setiawan; Yulfan Arif Nurohman; Waluyo Waluyo (ABDI MAKARTI, 2023)
Every country has a poverty problem. One way to reduce this problem is by empowering communities with a productive waqf model. This service aims to provide education and assistance to the community in managing productive waqf. The object of service is the community at the Al-Hidayah mosque congregation, Wonogiri Village, Kaliwungu District, Semarang Regency. The service approach uses the ABCD model, namely Asset Based Community Development. Community service is carried out in 3 ways, namely conducting FGD, socialization and mentoring. The results showed that the community began to have a good awareness in managing waqf in the form of goat livestock. Although several problems arise such as feed supply chain constraints during the drought and suboptimal kendang facilities. SWOT analysis shows the potential for economic improvement if carried out sustainably.